Phylogeny and Adaptive Radiation of the Neograptina (Graptoloida) During the Hirnantian Mass Extinction and Silurian Recovery - Melchin, M. J.; Mitchell, C. E.; Naczk-Cameron, A.; Fan, J. X. (樊隽轩); Loxton, J. (Proceedings of the Yorkshire Geological Society, 2011)
Cladistic analysis of some Hirnantian (latest Ordovician) and Rhuddanian-Aeronian (early Silurian) biserial graptolites and basal monograptids has been undertaken in order to test hypotheses of the relationships among the Neograptina ('normalograptids' and their descendents) and to provide a phylogenetic framework for understanding the early Silurian adaptive radiation of graptoloids. It is clear that Silurian graptolite faunas are dominated by two major clades, here named the superfamilies Retiolitoidea and Monograptoidea. Several other lineages whose basal relationships are unresolved, including Normalograptus and Metaclimacograptus, persisted through much of the Llandovery. The Retiolitoidea includes some taxa previously assigned to the Normalograptidae, as well as petalolithids and retiolitids. The Monograptoidea includes akidograptids, dimorphograptids, the uniserial monograptids, as well as stem taxa previously regarded as normalograptids. Both of these major clades had their origins in Late Ordovician time and began their diversification within the Hirnantian-early Rhuddanian, in step with the two main phases of the Hirnantian Mass Extinction. The Neograptina also exhibit an additional interval of accelerated turnover in the Rhuddanian during which the characteristic Silurian fauna largely replaced the Hirnantian Neograptina. One new family, Neodiplograptidae, and four new genera are described: Avitograptus, Rickardsograptus, Korenograptus and Paramplexograptus.